Olika metoder och tekniska hjälpmedel för att bestämma bevattningstidpunkt - Nilsson, Andreas (2005)
This examination work on studies and research in articles is mostly from other countries. The purpose of the examination work have been to find out if there are any means you can work with to find out when its time to start irrigation, how they works and if they are credible. In Sweden there is not many means for decide when it's time to irrigate and how much water you should appear. Swedish farmers think they have so much experience that they don't need techniques like this. They decide time for irrigation just with look at the crop and feel in the soil. The economy in Swedish farming is getting harder and harder. For good paying you must have a really good quality on the crop. It's easier to get a high quality on the crops if you now how much water it is in the soil. If you can measure the soil water you don't risk a water stress on the plants and leaks of nitrogen. The results off soil moisture sensors accuracy is that the usual sensor is good enough to decide when it's time to start irrigation and the amount of water. The accuracy of the results depends on how well they suits the soil. Soil contact is very important when you install your sensor. Air hole and stones can not be near the sensor if you should get credible results. You can even decide irrigation with water budget, this don't need any sensitive installation. This is a simple and reliable method but you must reading it of regular and manual. You never take consideration to how hard the soil holding the water.